Psychological Mechanisms for Creation Professional Orientation of the Personality - VINARCHIK, ELENA (Journal of Education, Technology and Computer Science, 2017)
Conscious choice of profession determines the success of learning, the formation of a stable professional orientation of each student. Requires an individual approach and maximum use of the full Arsenal of technologies aimed not only at increasing the level of students’ knowledge, but also on the development of professional identity of future specialists.